Analisis Miskonsepsi Siswa melalui Five-Tier Diagnostic Test pada Materi Kinematika Gerak Berbasis Quizziz - Ria Ananda; Fajrul Wahdi Ginting; Arlin Maya Sari; Safriana Safriana; Tulus Setiawan (Lembaga Bale Literasi, 2025)
The study investigated high school students' misconceptions regarding the concept of Kinematics, using the Five-Level Diagnostic Test to identify and analyze these misconceptions. The core problem discussed is the constant misunderstanding of basic physics concepts, which hinders student learning outcomes and conceptual understanding. This study uses a qualitative descriptive methodology, combining diagnostic tests, interviews, and observations to collect comprehensive data on student misconceptions. This multi-faceted approach allows for a deeper understanding of the factors that contribute to these misconceptions, including pedagogical and environmental influences. The findings revealed that a large number of students struggled with the concept of Kinematics, especially in determining speed and speed changes. The study concluded that misconceptions arise not only from cognitive limitations but also from inadequate teaching strategies. To address this problem, the study recommends the implementation of Problem-Based Learning (PBL) with scaffolding techniques to improve conceptual understanding and reduce misunderstandings effectively